The Source Of Control (control) And Its Relationship To The Skill Performance Of Handball Players - رابحي أمحمد; قندوز هشام (sports creativity, 2025)
The source of control is considered one of the modern psychological factors that play a vital and important The study aims to highlight the relationship between the source of control (control) and the skill performance of U19 handball players. The conclusion reached in the end is that the source of internal control for players who attribute success in skill performance is due to external forces from the internal psychological environment, where the dominant dimension of handball players is no longer. And that the source of internal control for players who cherish success in skill performance is due to the internal forces of the athlete itself, which is the dominant dimension for handball players. There is also no statistically significant relationship between the source of external control and the skill performance of handball players, meaning that handball players do not depend on the perceptions associated with their behavior and characteristics from external control (external control source).